Kimura’s disease: a diagnostic and therapeutic enigma - Bharat, Vinay; Gupta, Abhishek; Bansal, Rani; Gupta, Priya; Gupta, Mamta (International Journal of Research in Medical Sciences, 2018)
Kimura’s disease is a rare chronic inflammatory disorder present in 2nd and 3rd decade. It has a predilection for head and neck region presenting as a slowly growing painless swelling. It is usually accompanied by peripheral eosinophilia and elevated serum IgE and hence it was initially thought to be of allergic origin. Histologically the lesions are characterized by reactive hyperplasia of lymph nodes, eosinophilic infiltration and increase in postcapillary venules. Authors have reported a male patient with a slowly growing right sided neck swelling which is recurring even after course of steroids and excision done twice at an interval of 6 months. Kimura’s disease although a benign Lymphoid disorder but the incidence of recurrence despite taking treatment is a cause of much concern for the patient.